GROUPING STUDENT ACHIEVEMENT DATA IN A DECISION MAKING SYSTEM USING THE WEIGHT PRODUCT METHOD - Fajri, T. Irfan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Royal Kisaran, 2024)
Abstract: Information, modeling, and data manipulation systems are called decision support systems (DSS). When there is uncertainty about the best course of action in semi-structured or unstructured situations, the system is utilized to support decision-making. There are various approaches available for producing decision support systems, one of which is the Weighted Product (WP) Method. With the Weighted Product (WP) approach, attribute ratings are connected by multiplication; however, each attribute's rating must first be increased to the power of the attribute's weight. The normalizing process is same to this one. SPK procedure to choose the winners of the scholarships. Scholarship information from MTS Swasta Alwasliyah Simpang Merbau can be saved in the Decision Support System using this method. This way, in the event that an error arises when entering grades or scholarship information, the wrong information can be fixed without requiring the scholarship information to be re-input. Scholarships are presents to individuals in the form of financial aid intended to be utilized toward their ongoing educational pursuits. Keywords : decision support system; students; weighted product method Abstract: Sistem informasi, pemodelan, dan manipulasi data disebut sistem pendukung keputusan (DSS). Ketika terdapat ketidakpastian mengenai tindakan terbaik dalam situasi semi-terstruktur atau tidak terstruktur, sistem digunakan untuk mendukung pengambilan keputusan. Terdapat berbagai pendekatan yang tersedia untuk menghasilkan sistem pendukung keputusan, salah satunya adalah Metode Weighted Product (WP). Dengan pendekatan Weighted Product (WP) memiliki konsep yang sederhana untuk menentukan pembobotan terhadap kriteria yang memiliki nilai hampir sama sehingga dalam penentuan penerima beasiswa dapat mudah dilakukan walaupun dengan data yang banyak. Metode Weighted Product (WP) dengan kriteria penilaian akademik, sikap dan tanggung jawab dan hasil perhitungan tertinggi menggunakan sistem yaitu 0.27. Sehingga dapat diterapkan untuk menyeleksi siswa-siswi berprestasi dan untuk menerapkan pemilihan siswa-siswi berprestasi secara online dengan disebarkan kedalam kelas. Keywords: metode weighted product; sistem pendukung keputusan; siswa